(untitled) (Journal of Comparative & International Higher Education, 2023)
This study uses a correlation, quantitative approach to understand the relationship between academic stress, adjustment, and social support. International students from various colleges and universities across India participated in the study. Analysis revealed significant relationships between academic stress, academic lifestyle, academic achievement, and social support. The adjustment was categorized into academic lifestyle, academic achievement, and academic motivation. Better adjustment and quality social support systems led to a decrease in academic stress. Multiple regression analysis showed academic lifestyle as a significant predictor of perceived academic stress. The academic motivation was directly proportional to an increase in academic stress (p<0.05). We found a significant difference in students’ academic motivation based on gender. The findings of this study call for adopting a holistic approach to reduce international students’ academic stress and adjustment concerns. Also, steps to ensure social support can enrich students’ academic journey in a foreign land.